Primary Lateral Sclerosis and Early Upper Motor Neuron Disease: Characteristics of a Cross-Sectional Population. Issue 3 (March 2016) - Fournier, Christina N.; Murphy, Alyssa; Loci, Lorena; Mitsumoto, Hiroshi; Lomen-Hoerth, Catherine; Kisanuki, Yasushi; Simmons, Zachary; Maragakis, Nicholas J.; McVey, April L.; Al-Lahham, Tawfiq; Heiman-Patterson, Terry D.; Andrews, Jinsy; et al.
Abstract: Objectives: The goals of this study were to characterize clinical and electrophysiologic findings of subjects with upper motor neuron disease and to explore feasibility of clinical trials in this population. Methods: Twenty northeast amyotrophic lateral sclerosis consortium (northeast amyotrophic lateral sclerosis) sites performed chart reviews to identify active clinical pure upper motor neuron disease patients. Patients with hereditary spastic paraplegia or meeting revised El Escorial electrodiagnostic criteria for amyotrophic lateral sclerosis were excluded. Patients were classified into 2 groups according to the presence or absence of minor electromyography (EMG) abnormalities. Results: Two hundred thirty-three subjects with upper motor neuron disease were identified; 217 had available EMG data. Normal EMGs were seen in 140 subjects, and 77 had minor denervation. Mean disease duration was 84 (±80) months for the entire cohort with no difference seen between the 2 groups. No difference was seen in clinical symptoms, disability, or outcome measures between the 2 groups after correcting for multiple comparisons. Conclusions: Minor EMG abnormalities were not associated with phenotypic differences in a clinical upper motor neuron disease population. These findings suggest that subtle EMG abnormalities can not necessarily be used as a prognostic tool in patients with clinical upper motor neuron disease. This study also demonstrates the availability of a large number of patients with upper motor neuron diseases within the northeast amyotrophic lateral sclerosis network and suggests feasibility for conducting clinical trials in this population.